Experimental Test of Flexural Strength of Green Concrete Using 0%, 10%, 30% Waste Tire Rubber Powder as a Substitute for Fine Aggregate - Nugroho, Guntur (PT Akselerasi Karya Mandiri, 2025)
The increasing demand for sustainable construction has driven the development of green concrete incorporating recycled waste materials. This study investigates the flexural strength of concrete partially substituting fine aggregate with waste tire rubber powder at 0%, 10%, and 30% replacement levels. Concrete beams measuring 150 mm × 150 mm × 600 mm were cast and tested at 28 days using third-point loading in accordance with ASTM C78. The experimental results show that the 10% rubber powder mix achieved the highest flexural strength, with a 52.5% increase compared to the control. In contrast, the 30% mix exhibited a moderate reduction in strength. Despite the slight decline at higher replacement levels, all mixes retained acceptable structural performance and workability without chemical admixtures. The findings suggest that partial substitution of fine aggregate with rubber powder up to 10% can enhance flexural behavior while promoting environmentally friendly concrete solutions.